Vizije prihodnosti mest - Poljak Istenič, Saša (Urbani izziv, 2022)
Due to overpopulation, pollution, noise, and other ecological and social problems, cities face a worsening quality of urban life, which requires effective planning of their futures. Urban visions as an aspect of strategic planning can be a starting point for a radical transformation of how towns develop into cities of the future that successfully address current challenges. This article, deriving from the anthropology of the future and planning, analyses how cities imagine their futures and how they narrate it. It compares the visions of eight Slovenian and Croatian cities – Ljubljana, Zagreb, Koper, Rijeka, Maribor, Kutina, Nova Gorica, and Hvar – and assesses how they understand the concept of sustainable development and take into account its principles (economic, environmental, social, and cultural sustainability). Discourse analysis reveals that visions often remain on paper only, with undefined elements of sustainability and values. They repeatedly instrumentalize urban realities – that is, natural and cultural resources – for their goals. To achieve better cooperation of residents in helping create cities of the future, visions should be more long-term and imaginative.
Keywords: anthropology of the future; antropologija prihodnosti; cities’ visions; Croatia; Hrvaška; Slovenija; urban planning; urbano načrtovanje; vizije mest